K-Hammer percutaneous fixation: a novel technique for preventing iatrogenic ulnar nerve injury in pediatric supracondylar humeral fractures - Zhou, Yijun; Bai, Xiaoan; Li, Changhong; Zhou, Mi; Bai, Fan; Chen, Jiang; Sun, Guanwen (Frontiers in Pediatrics, 2025)
BackgroundThis study evaluated the therapeutic efficacy of a novel percutaneous Kirschner wire (K-wire) fixation combined with the K-Hammer technique in pediatric patients with supracondylar humeral fractures.MethodsThis retrospective cohort study included 34 pediatric patients [13 males (38.24%); 21 females (61.76%); mean age 5.82 ± 2.54 years] with acute extension-type supracondylar humeral fractures (diagnosed ≤7 days post-trauma). Under general anesthesia, fractures underwent fluoroscopy-guided closed reduction and percutaneous fixation: two lateral-entry 1.5–2.0 mm K-wire provided initial stabilization, followed by a third medial-entry K-wire inserted using the K-Hammer technique to achieve a biomechanically optimized cross-pinning configuration. Postoperatively, the elbow was immobilized in a 90° functional position with a long-arm fiberglass cast for 4 weeks.ResultsOver a mean follow-up of 12.24 ± 4.45 months (range: 6–23 months), functional outcomes per Flynn's criteria were excellent in 32 patients (94.12%), good in 2 (5.88%), and fair in 0 (0%). No cases of secondary displacement, osteonecrosis, or major complications—such as nonunion, iatrogenic neurovascular injury, myositis ossificans, or chronic elbow dysfunction—were observed during postoperative monitoring.ConclusionsThe K-Hammer-assisted medial K-wire insertion provides a streamlined, reproducible approach for managing irreducible extension-type pediatric supracondylar humeral fractures. It effectively mitigates iatrogenic ulnar nerve injury, minimizes soft tissue trauma, ensures biomechanical stability, and promotes optimal long-term elbow kinematics.